Winds of Change in Rajasthan and Madhya Pradesh during 2019 Indian General Elections: An Appraisal - Sehgal, Manohar L. (Advances in Social Sciences Research Journal, 2018)
The seeds of ’Opposition Unity’ sown by the two regional parties- the S.P and B.S.P of U.P sprouted in Bihar and have, now, grown up in the Karnataka state by the Congress and J.D(S) combine where Congress being magnanimous to gift the Chief Minister ship of the state to the junior partner, the J.D(S) . By the time, the message is loud and clear that ’Modi can be defeated only if all the opposing parties of a particular state unites against his B.J.P’. Thus the ’United Opposition’, in all probability, will face the mighty B.J.P together in 2019 General Election in the states of Rajasthan and Madhya Pradesh. The present study discusses the various possibilities by which the parties opposed the B.J.P are expected to take on the ruling party though these states , for the last over more than two decades, have been bipolar between B.J.P and Congress in respect to the their state politics . B.S.P, though, always been a poor third in M.P. but has a strong vote bank in some pockets of this state. So in combination with other parties, it may become lethal for B.J.P and may bring a pleasant surprise for the ’United Opposition’ in general and the Congress in particular. Modi’s wave might have been on the wane, but only to a small extent. So it will be a walk on the razor’s edge both for the B.J.P and the parties opposed to the B.J.P.